Efektivitas Perkecambahan Kemiri dengan Metode Konvensional - Jayadi; Irundu, Daud; Idris, Andi Irmayanti (Program Studi Kehutanan Fakultas Pertanian dan Kehutanan Universitas Sulawesi Barat, 2022)
Candlenut is a native plant of Indo-Malaysia and has been introduced to the pacific islands since ancient times. The constraint experienced by the community is the lack of seeds for candlenut cultivation, so this study aims to determine the effectiveness of water immersion and combustion treatments for candlenut seed germination and to obtain the most effective treatment in breaking the candlenut dormancy period. The method used in this research is the method of Randomized Block Design (RAK). The results obtained from this study were the combustion treatment was better than the hot water immersion treatment and the best was group III or large seeds.